Reconstruction of the Function of Takhsis in Ushul Fiqh in Contemporary Muslim Society - Ahmad, Upi Sopiah; Syahnan, Mhd.; Khoiri, Nisful; Tanjung, Dhiauddin (Hakamain: Journal of Sharia and Law Studies, 2025)
This study aims to reconstruct the function of takhsis in ushul fiqh within contemporary Muslim society by critically examining its conceptual role and practical application in modern Islamic legal reasoning. The research employs a qualitative normative methodology through textual and analytical approaches, focusing on classical ushul fiqh literature, contemporary scholarly works, and selected fatwa and legal discourses that reflect current socio-legal realities. Data are analyzed by comparing classical formulations of takhsis with contemporary interpretations to identify patterns of continuity, shift, and methodological tension. The findings indicate that the function of takhsis in contemporary practice tends to be applied in a limited and formalistic manner, often emphasizing textual restriction while neglecting broader contextual, social, and purposive considerations. This condition results in interpretive rigidity and difficulties in responding effectively to social change, legal pluralism, and new legal problems faced by Muslim societies today. The study finds that takhsis requires functional reconstruction by repositioning it not merely as a textual limiting tool, but as a dynamic methodological instrument that operates in harmony with contextual analysis and the objectives of Islamic law. The study concludes that such reconstruction is essential to maintain the relevance and adaptability of ushul fiqh in contemporary contexts. Academically, this research contributes to the development of ushul fiqh studies by offering a systematic reinterpretation of takhsis that bridges classical legal theory and contemporary legal challenges, and by enriching ongoing discussions on Islamic legal methodology, reform, and contextual interpretation.